Significance of Mycobacterium tuberculosis antigen expression in cerebrospinal fluid monocytes in diagnosing tuberculous meningitis - Fu-Xia Song; Xu-Wen Sun; Xiao-Tong Wang; Yu Nai; Zhu-Li Liu (Wolters Kluwer Medknow Publications, 2014)
Background: The aim of this study was to investigate the significance of positive expression of Mycobacterium tuberculosis, (MTB) antigen in the cerebrospinal fluid (CSF) monocytes in diagnosing tuberculous meningitis (TBM). Materials and Methods: A total of 50 inpatients of TBM, 30 viral meningitis and 20 healthy controls were studied at the 1 st , 2 nd , and 4 th week during their treatment course. Immunohistochemical assay were used to detect early secreted antigenic target 6 (ESAT-6) positive cells, and positive cases were also observed. Results: The percentage of positive cases and positive cells of ESAT-6 in CSF monocytes were all higher in the 1 st and 2 nd week than in the 4 th week in TBM patients (P < 0.01); and percentage of positive cases and positive cells of MTB antigen in CSF monocytes were higher in TBM patients than in viral meningitis and health control in the 1 st and 2 nd week (P < 0.01). The sensitivity was 90% and the specificity was 92% in the early stage (within 2 weeks) of TBM. Conclusion: The positive expression of ESAT-6 in CSF monocytes is helpful for the early diagnosis of TBM.